2013
DOI: 10.1111/jpr.12021
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Two‐Dimensional Mood Scale for self‐monitoring and self‐regulation of momentary mood states

Abstract: The purpose of this study was to develop a measure for self-monitoring and self-regulation of momentary mood states. The Two-Dimensional Mood Scale (TDMS), consisting of eight words selected on the basis of pleasure and arousal, was created as an efficient measure of self-monitoring. In Study 1, the validity and reliability of the TDMS were examined by administering the measure to 904 university students. Structural equation modeling revealed that mood states were constructed of two components, arousal and ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 18 publications
0
67
1
1
Order By: Relevance
“…A Two-Dimensional Mood Scale (TDMS-ST) [5], POMS [6], and a verification test were applied for assessment. The Two-Dimensional Mood Scale is a psychological scale that measures psychological state (mood) upon response to eight questions.…”
Section: Assessment Methodsmentioning
confidence: 99%
“…A Two-Dimensional Mood Scale (TDMS-ST) [5], POMS [6], and a verification test were applied for assessment. The Two-Dimensional Mood Scale is a psychological scale that measures psychological state (mood) upon response to eight questions.…”
Section: Assessment Methodsmentioning
confidence: 99%
“…and "excitement-depression"). Sakairi et al (2013) reported that the psychological scale based on these evaluation axes, as shown in Figure 1, was a useful way to quantitatively describe the psychological state of the subject and its time sequential change. As shown in previous research, a psychological metric for measuring emotions is introduced and the measurement results using the scale are reduced by factor analysis.…”
Section: Evaluation Of Axes Of Emotionmentioning
confidence: 99%
“…Moreover, we postulated that exercise-induced changes of mood, such as arousal and pleasure levels that could be measured using psychological mood scales 15) , might be associated with exercise-induced change in executive function. Thus, combining the fNIRS neuroimaging method and the psychological measurements might provide insight into the possible physiological mechanisms underlying mild-exercise-enhanced executive function.…”
Section: Introductionmentioning
confidence: 99%